2019
DOI: 10.1111/acv.12477
|View full text |Cite
|
Sign up to set email alerts
|

The effect of knowledge, species aesthetic appeal, familiarity and conservation need on willingness to donate

Abstract: Environmental non-governmental organizations (ENGOs) largely select flagship species for conservation marketing based on their aesthetic appeal. However, little is known about the fundraising effectiveness of this approach or how it compares to ecosystem conservation campaigns that use habitat types as flagships. By performing a willingness to donate (WTD) survey of potential online donors from Finland, we identified which motivations and donor characteristics influence their preferences for a range of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 56 publications
5
38
1
Order By: Relevance
“…The same result was also revealed in the studies by Witt (2019) and Pedroso and Kungu (2019). Education and awareness has a positive consequence on personal maturity and will help to increase one's knowledge and could ultimately have an impact on the positive environmental thinking of a person (see Opacak and Wang, 2019;Rodella et al, 2019;Lundberg et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The same result was also revealed in the studies by Witt (2019) and Pedroso and Kungu (2019). Education and awareness has a positive consequence on personal maturity and will help to increase one's knowledge and could ultimately have an impact on the positive environmental thinking of a person (see Opacak and Wang, 2019;Rodella et al, 2019;Lundberg et al, 2019).…”
Section: Discussionsupporting
confidence: 64%
“…Choi and Fielding, 2013;Hultman et al, 2015;Rodella et al, 2019;Nie et al, 2019) showed that an individual WTP can be influenced by his/her age, gender, education, and income. Particularly, WTP can also be a function of the previous visit and visit preferences (Kamri et al, 2017), participation in environmental issues and knowledge of ecotourism and conservation (Han et al, 2011;Sadikin et al, 2017;Lundberg et al, 2019), and the level, and type of ecotourism activities, trekking, and nationality (Platania and Rizzo, 2018;Murphy et al, 2018). The present study, therefore examined the effect of attitudes towards conservation and ecotourism, environmental concern, and visit characteristics, besides the socio-demographic variables to provide a comprehensive model of visitors' WTP.…”
Section: Previous Valuation Studiesmentioning
confidence: 95%
See 2 more Smart Citations
“…This result shows how filmmakers or conservation agencies can highlight a particular species or conservation issue by dedicating more airtime to the topic. The lack of proactive actions stemming from Planet Earth 2 through charitable donations was not completely unexpected, as awareness is just one of many factors influencing these behaviors (Lundberg et al, 2019). Proactive actions in response to conservation messages are the result of complex social processes (de Lange et al, 2019) and may happen at a considerable lag, making it difficult to establish a cause-and-effect relationship.…”
Section: Discussionmentioning
confidence: 99%